1999
DOI: 10.1093/nar/27.13.2699
|View full text |Cite
|
Sign up to set email alerts
|

Stability of G,A triple helices

Abstract: In this work we selected double-stranded DNA sequences capable of forming stable triplexes at 20 or 50 degrees C with corresponding 13mer purine oligonucleotides. This selection was obtained by a double aptamer approach where both the starting sequences of the oligonucleotides and the target DNA duplex were random. The results of selection were confirmed by a cold exchange method and the influence of the position of a 'mismatch' on the stability of the triplex was documented in several cases. The selected sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…TTSs with lower guanine concentration a gradual decline is observed similar to what was observed for the triplex disfavoring conditions (Figure 3f), which is consistent with an unstable and weak triplex interaction. These observations are in accordance with findings from another study which showed that G-rich TTSs (with ~80% G-content) are necessary for triplex formation 13 . Hence, our results suggest that G-rich TTS variants lead to a stronger, more specific and pH-independent triplex interaction with TFO libraries that contain a few highly-specific variants, compared to TTS variants Figure 6).…”
Section: G-rich Tfos Form Stronger Triplexes With G-rich Ttsssupporting
confidence: 93%
See 1 more Smart Citation
“…TTSs with lower guanine concentration a gradual decline is observed similar to what was observed for the triplex disfavoring conditions (Figure 3f), which is consistent with an unstable and weak triplex interaction. These observations are in accordance with findings from another study which showed that G-rich TTSs (with ~80% G-content) are necessary for triplex formation 13 . Hence, our results suggest that G-rich TTS variants lead to a stronger, more specific and pH-independent triplex interaction with TFO libraries that contain a few highly-specific variants, compared to TTS variants Figure 6).…”
Section: G-rich Tfos Form Stronger Triplexes With G-rich Ttsssupporting
confidence: 93%
“…Given the specificity in formation of triplexes 6,7,9 , Moser and Dervan 8 developed short DNA-based triplex-forming oligonucleotides (TFOs) that are typically 15-30 nt long and form triplexes with polypurine stretches of the dsDNA termed triplex target site (TTS). Due to their specificity in targeting dsDNA, TFOs were subsequently used to identify triplex rules 13,14 and applied as biotechnological tools in vitro and in vivo to regulate transcription [15][16][17][18] , control recombination events 19 and induce triplex-directed mutagenesis [20][21][22] . Despite extensive amount of work to establish TFOs as therapeutic agents, triplex formation in vivo mostly was attenuated and the expected biological function was limited 23,24 .…”
mentioning
confidence: 99%
“…The stability of triplexes formed with G‐rich TFOs has been shown to be very high, particularly with (A,G)‐containing TFOs, but has also been found to be highly unpredictable. Attempts to clarify the basis of such stability have been made over the last few years, and the base composition of the target sequence was found to play an important role13, 14. Moreover, spectroscopic studies comparing thermodynamic parameters for TFOs with different base compositions [(A,G), (T,G) and (T,C)] revealed that (A,G) and (T,G) triplexes are entropy driven rather than enthalpy driven as compared to (T,C) triplexes15.…”
Section: Triple Helix Formation: From Formation To Irreversibilitymentioning
confidence: 99%
“…The DNA triplex stability is greater, longer the PR length (Collier and Wells, 1990). Therefore, it directly depends on the length of PR, however, interruption by a single pyrimidine in the PR, destabilizes the triplex by many fold (Debin et al, 1999). A well documented neurodegenerative disorder FRDA is identified with purine repeat in FXN gene ranging from 198-3600 (Swarup et al, 2011) and in rare cases, a repeat can be as long as 5100 (Wells, 2008).…”
Section: Resultsmentioning
confidence: 99%